Stress and self-esteem among nursing students at private medical college, Chitwan - Shrestha, Swostika; Ghimire, Srijana (Journal of Chitwan Medical College, 2019)
Background: Stress and self-esteem are common issues that everyone has to cope with at some time in their lives and they could also affect other things going on in a person’s’ life. The objective of the study is to identify the stress and self-esteem among nursing students. Methods: A descriptive cross-sectional study was carried out among B.Sc. Nursing students, Chitwan Medical College. The data was collected by using structured questionnaire within 2 weeks. Obtained data were analyzed using IBM SPSS version 16.0. Descriptive statistics (mean, frequency, percentage and standard deviation) and inferential statistics (chi-square and correlation) were used for data analysis. Results: Out of 116 respondents, 23.3%, 25.9%, 25.9% and 25.0% were from first, second, third and fourth year respectively. More than half i.e. 50.9% of the respondents had high stress. Respondents had faced higher (68.1%) in teacher related stress followed by peer stress 67.2% and self-inflict 66.0%. About 61.2% of the respondents had low self-esteem. There was higher stress in first year students then other. The fact is that as the academic year increases, students become more familiar to the learning environment and able to cope better. There was statistical significant association between stress among nursing students and habit of problem sharing (p=0.04). Conclusions: It is concluded that respondents have high level of stress and low level of self-esteem. Therefore, intervention for increasing self-esteem and decreasing stress should be conducted by the college administration.